Două cazuri de divorţ în oraşul Arad în secolul al XVIII-lea - Ghita, Eugen (2010)
Abstract: The two documents which are the subject of the present study, made to share property in the event of divorce, help to form an image on various aspects of daily life, poorly known from other sources: household size, land property, earnings in marriage furniture, tools, animals, prices, food, secular and religious involvement of the private life etc. In addition to legal information, both inventories, which stood at the base of documents on which the property was to be divided, reveal another perspective on social history of Arad in the late eighteenth century